2021
DOI: 10.1111/jcpp.13420
|View full text |Cite
|
Sign up to set email alerts
|

The role of child negative emotionality in parenting and child adjustment: Gene–environment interplay

Abstract: Background: Evocative gene-environment correlation (rGE) describes a process through which children's heritable characteristics influence their rearing environments. The current study examined whether heritable influences on parenting and children's behavioural outcomes operate through child negative emotionality. Method: Using data from the Early Growth and Development Study, we examined associations among adoptive parent reports of child anger and sadness at 4.5 years, adoptive parents' hostile and warm pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“…In relation to the effect of negative reactivity on social skills, findings confirmed previous evidence (e.g., Shewark et al, 2021;Tung et al, 2018). The relevance of considering children's individual characteristics when assessing their outcomes in middle childhood is then emphasized.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In relation to the effect of negative reactivity on social skills, findings confirmed previous evidence (e.g., Shewark et al, 2021;Tung et al, 2018). The relevance of considering children's individual characteristics when assessing their outcomes in middle childhood is then emphasized.…”
Section: Discussionsupporting
confidence: 78%
“…Parenting processes may be moderated or mediated by the child's individual characteristics or, conversely, they may moderate or mediate the child's individual characteristics (Reiss et al, 2013). Adoption is a natural research design that allows for the distinction of individual and context-based processes and contributes to the knowledge of the mechanisms through which children shape and are shaped by their rearing environments (Palacios, 2018;Shewark et al, 2021). However, research in this field has mostly focused on the child's heritable characteristics that influence parenting (e.g., Liu et al, 2020), the influence of child-evoked parenting on child's developmental outcomes (e.g., Harold et al, 2013), and the moderation of the child's individual characteristics in the relationship between parenting and child's outcomes (e.g., Leve et al, 2013;Reiss et al, 2013;Shewark et al, 2021).…”
Section: Adoptees' Social Skills: a Hybrid Dyadic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, we tested theory‐driven models: the genetic nurture model has been tested in a similar form for other aspects of the home environment and other outcomes (e.g., Wertz et al., 2019). The evocative gene–environment correlation model has recently been tested using adoption data (Shewark et al., 2021). Nonetheless, the directions of effects might be different.…”
Section: Discussionmentioning
confidence: 99%
“…The bidirectional nature of the parent–child relationship has been known for several decades. Many studies have found that children both shape and are shaped by relationships with their parents (e.g., Shewark et al, 2021; Russell, 2014). As with all relationships, parent–child interactions unfold on a moment-to-moment basis and are guided by the behavior and responses of both members of the dyad.…”
mentioning
confidence: 99%